Continental‐scale Impacts of Livestock Grazing on Ecosystem Supporting and Regulating Services - Eldridge, David J.; Delgado‐Baquerizo, Manuel (Land degradation & development, 2017)
Grazing by livestock supports millions of people worldwide, particularly in drylands, but has marked negative effects on ecosystem services and functions. In Australia, its effects on ecosystem services have not been fully quantified. We examined the extent to which grazing by livestock influenced supporting (productivity, habitat for organisms and biodiversity) and regulating (carbon cycling and hydrological function) services, using data from published and unpublished studies on livestock grazing from a large number of sites across Australia. Grazing reduced our measure of supporting services by about 20% and regulatory services by 8%. On average, grazing reduced plant productivity by 40%, habitat value by 20%, and biodiversity, hydrological function and carbon sequestration by about 10%. Habitat and productivity showed strong declines with increasing grazing intensity, and carbon showed strong declines at the lowest and highest contrasts. Hydrological function and biodiversity did not decline with increasing grazing intensity. Overall, the results indicate that livestock grazing leads to substantial degradation at a continental scale by reducing ecosystem services associated with habitat provision, biodiversity, and soil and water functions. Management of livestock grazing will be critical if we are to retain functional levels of ecosystem services into the next century. Copyright © 2016 John Wiley & Sons, Ltd.